2012
DOI: 10.3109/09553002.2012.638358
|View full text |Cite
|
Sign up to set email alerts
|

A frequency-based gene selection method to identify robust biomarkers for radiation dose prediction

Abstract: The genes identified are potential robust biomarkers, which are particularly suitable for dose level discrimination at a window of time that would be appropriate for life-saving medical triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
4
37
1
Order By: Relevance
“…All non-irradiated samples were correctly classified as unirradiated controls by the KNN method. Overall, the obtained dose estimations obtained by KNN classification were very satisfying keeping in mind that the classification is not based on the calibration sample data but on microarray data from 2008-2011 derived from cultured peripheral blood lymphocytes from six nonrelated blood donors (for more detail, see Boldt et al 2012).…”
Section: Dose Estimationmentioning
confidence: 63%
See 4 more Smart Citations
“…All non-irradiated samples were correctly classified as unirradiated controls by the KNN method. Overall, the obtained dose estimations obtained by KNN classification were very satisfying keeping in mind that the classification is not based on the calibration sample data but on microarray data from 2008-2011 derived from cultured peripheral blood lymphocytes from six nonrelated blood donors (for more detail, see Boldt et al 2012).…”
Section: Dose Estimationmentioning
confidence: 63%
“…It has been reported many times that the quantification of gene expression in response to radiation exposure by microarray technology is robust and reliable (Paul & Amundson 2008;Boldt et al 2012;Knops et al 2012), and the obtained gene signatures derived in ex situ irradiated blood are shown to be predictive for the radiation dose in vitro as well as in vivo (Paul et al 2011). The gene signature developed by Boldt et al (2012) was reported to be robust in terms of dose prediction.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations